1984
DOI: 10.1007/bf02913969
|View full text |Cite
|
Sign up to set email alerts
|

Location of the proanthocyanidins in the barley grain

Abstract: A vanillin-HCl staining has been used to locate the proanthocyanidins in mature barley grains. These flavanoids were found to be concentrated in the seed coat (testa) just outside the aleurone layer in the 7 varieties with yellow coloured grains investigated. The seed coats of 10 proanthocyanidin-free barley mutants belonging to 4 different gene loci did not stain with vanillin-HC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 8 publications
0
48
1
2
Order By: Relevance
“…Surprisingly, the seed of tt2-2 harbored a buffcolored seed coat (Figure 2A), which clearly differed from the golden yellow seed of the three other tt2 mutant alleles. Using a vanillin test, which stains proanthocyanidins as well as the catechin and leucoanthocyanidin precursors dark red in wild-type seed (Aastrup et al, 1984) (Figure 2E), we confirmed the presence of a very small amount of these products in immature seed of tt2-2 ( Figure 2G). Conversely, no red stain appeared in tt2-3 seed ( Figure 2F).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Surprisingly, the seed of tt2-2 harbored a buffcolored seed coat (Figure 2A), which clearly differed from the golden yellow seed of the three other tt2 mutant alleles. Using a vanillin test, which stains proanthocyanidins as well as the catechin and leucoanthocyanidin precursors dark red in wild-type seed (Aastrup et al, 1984) (Figure 2E), we confirmed the presence of a very small amount of these products in immature seed of tt2-2 ( Figure 2G). Conversely, no red stain appeared in tt2-3 seed ( Figure 2F).…”
mentioning
confidence: 52%
“…The vanillin test (Aastrup et al, 1984) was performed by direct incubation of immature siliques or root samples in a freshly prepared solution of 1% (w/v) vanillin (4-hydroxy-3-methoxybenzaldehyde; Sigma) in 6 N HCl for 30 min at room temperature. Under acidic conditions, vanillin turns red upon binding to flavan-3,4-diols (leucoanthocyanidins) and flavan-3-ol (catechins), which are present as monomers or as terminal subunits of proanthocyanidins (Deshpande et al, 1986).…”
Section: Histological Analysismentioning
confidence: 99%
“…Ovules and seeds were dissected from pistils and siliques, respectively, and incubated in an acidic solution (6 N HCl) of 1% (w/v) vanillin (Sigma-Aldrich) at room temperature (Aastrup et al, 1984). Vanillin reacts in the presence of PAs that specifically accumulate in the endothelium layer of the seed coat, generating a red product (Debeaujon et al, 2003).…”
Section: Whole-mount Staining For Detection Of Pasmentioning
confidence: 99%
“…Recently, many elite barley cultivars with high pearling quality such as Syunrai (Kuwabara et al 1994), Ichibanboshi (Ito et al 1995), Nishinohoshi (Sasaki et al 1999) and Fiber-Snow (Ushiyama et al 2004) have been bred in Japan; however, no food barley cultivar without after-cooking discoloration has been bred anywhere in the world including Japan. Barley grains contain numerous polyphenolic compounds including catechin and proanthocyanidin in the husks, pericarp, testa and aleurone layers (Aastrup et al 1984, Nordkvist et al 1984. Oxidation of phenolic compounds to o-quinones causes discoloration in food (Sapers 1993).…”
Section: Introductionmentioning
confidence: 99%